Answer:
10
Step-by-step explantion
Simplifying
2x + 3 + 25 = 3x + -17
Reorder the terms:
3 + 25 + 2x = 3x + -17
Combine like terms: 3 + 25 = 28
28 + 2x = 3x + -17
Reorder the terms:
28 + 2x = -17 + 3x
Solving
28 + 2x = -17 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
28 + 2x + -3x = -17 + 3x + -3x
Combine like terms: 2x + -3x = -1x
28 + -1x = -17 + 3x + -3x
Combine like terms: 3x + -3x = 0
28 + -1x = -17 + 0
28 + -1x = -17
Add '-28' to each side of the equation.
28 + -28 + -1x = -17 + -28
Combine like terms: 28 + -28 = 0
0 + -1x = -17 + -28
-1x = -17 + -28
Combine like terms: -17 + -28 = -45
-1x = -45
Divide each side by '-1'.
x = 45
Simplifying
x = 45